2015
DOI: 10.1007/s00253-015-6563-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CYP106A1 and CYP106A2 from Bacillus megaterium – identification of a novel 11-oxidase activity

Abstract: The CYP106A subfamily hydroxylates steroids, diterpenes, and triterpenes in a regioselective and stereoselective manner, which is a challenging task for synthetic chemistry. The well-studied CYP106A2 enzyme, from the Bacillus megaterium strain ATCC 13368, is a highly promising candidate for the pharmaceutical industry. It shares 63 % amino acid sequence identity with CYP106A1 from B. megaterium DSM319, which was recently characterized. A focused steroid library was screened with both CYP106A1 and CYP106A2. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Likewise, product P3, which was identified as a 2:3 mixture of 15β‐hydroxyprednisone and 1,2‐dihydro‐15β‐hydroxyprednisone displaying 11‐oxidation catalyzed by CYP106A1 (Scheme 1 ). The unusual 1(2)‐double bond hydrogenation has not been observed in our previous studies [22], hence, it was proposed to be the result of an uncharacterized enzyme present in the B. megaterium MS941 strain. It has been reported that 3‐ketosteroid‐dehydrogenases present in Nocardia , Mycobacterium and Actinobacter sp.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…Likewise, product P3, which was identified as a 2:3 mixture of 15β‐hydroxyprednisone and 1,2‐dihydro‐15β‐hydroxyprednisone displaying 11‐oxidation catalyzed by CYP106A1 (Scheme 1 ). The unusual 1(2)‐double bond hydrogenation has not been observed in our previous studies [22], hence, it was proposed to be the result of an uncharacterized enzyme present in the B. megaterium MS941 strain. It has been reported that 3‐ketosteroid‐dehydrogenases present in Nocardia , Mycobacterium and Actinobacter sp.…”
Section: Resultsmentioning
confidence: 48%
“…Since the previously identified substrates for the CYP106A1 11‐oxidation (corticosterone and cortisol) gave rise to multiple product formation [22], other 11β‐hydroxysteroid analogs were investigated to identify a selective 11‐keto product formation. The in vitro conversion of the pharmaceutically relevant glucocorticoids, prednisolone and dexamethasone, also resulted in several products (Table 1 , Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CYPs such as CYP106A1, CYP106A2, CYP109B1, CYP109E1, CYP154C3, CYP154C5, CYP260A1, and CYP260B1, originating from bacterial sources, are known to hydroxylate steroids . CYP154C8 shows high similarity with CYP154C3 (74 %) and CYP154C5 (66 %), both of which are reported to hydroxylate steroids at C16α.…”
Section: Introductionmentioning
confidence: 99%